Účinky antimikrobiálních peptidů - Komínková, Markéta; Zítka, Ondřej; Kizek, René (Journal of Metallomics and Nanotechnologies, 2014)
Organisms can produce substances which act as protection against the negative effects of microorganisms. Many of these substances belong among the peptides and represent an important mechanism of innate immunity. Peptides having activity against bacteria, fungi, parasites, viruses and cancer are collectively referred to as antimicrobial peptides (AMPs). Due to the increasing resistance of pathogenic microorganisms to antibiotic treatment, AMPs come to the forefront as a suitable alternative. Out of an antimicrobial activity, also the possible use for the treatment of fungal, parasite and virus diseases are studied. Also it has a significant potential use for the treatment of cancer, as some AMPs demonstrated significant antitumor activity.
Keywords: protinádorová aktivita; Antiparasitic Agents; peptidy; Peptides; Antimicrobial Cationic Peptides; antibakteriální látky; lidé; antiparazitární látky; Antiviral Agents; kationické antimikrobiální peptidy; Antifungal Agents; Antimicrobial Peptides; Antineoplastic Agents; Anti-Bacterial Agents; antimikrobiální peptidy; Humans; protinádorové látky; antivirové látky; antimikrobiální aktivita; antifungální látky